2021
DOI: 10.3389/fnut.2021.800932
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Antibiotic Resistance Genes in Bacterial Communities During Garlic Powder Processing

Abstract: Chinese garlic powder (GP) is exported to all countries in the world, but the excess of microorganisms is a serious problem that affects export. The number of microorganisms has a serious impact on the pricing of GP. It is very important to detect and control the microorganism in GP. The purpose of this study was to investigate the contamination and drug resistance of microorganisms during the processing of GP. We used metagenomics and Illumina sequencing to study the composition and dynamic distribution of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Metagenomics approaches have been employed to investigate the content and dynamic distribution of ARGs, as well as the microbial population, in three types of factory-processed Chinese garlic powder (GP) products [ 12 ]. The findings revealed that 126 ARG genes from 11 different ARG species were detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomics approaches have been employed to investigate the content and dynamic distribution of ARGs, as well as the microbial population, in three types of factory-processed Chinese garlic powder (GP) products [ 12 ]. The findings revealed that 126 ARG genes from 11 different ARG species were detected.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that 126 ARG genes from 11 different ARG species were detected. With the processing of GP, the expression of ARGs increased at first and later decreased [ 12 ]. Since garlic is added to food, this finding raises concern about the possible emergence of antibiotic-resistant strains from dietary supplies.…”
Section: Introductionmentioning
confidence: 99%